FRI0097 Factors Associated with Major Depressive Disorder in Rheumatoid Arthritis Patients. (10th June 2014) - Lisitsyna, T.A.; Veltishchev, D.; Gerasimov, A.; Seravina, O.; Kovalevskaya, O.; Zeltyn, A.; Krasnov, V.; Nasonov, E.
Abstract : Background: Psychiatric disorders occur in rheumatoid arthritis (RA) patients very often. It is considered that major depressive disorder (MDD) in RA is stress-related and associated with disease activity and chronic pain. Objectives: to determine the factors associated with MDD in RA pts by linear regression analysis. Methods: 125 RA pts were enrolled in this study. 86% RA pts were women with a mean age of 47.4±11.3 (M±m). The disease activity was assessed by DAS28 score. 52% of RA pts had a high activity of disease (DAS28>5, 1). 67% RA pts were taking prednisone in mean dose 5±2.7 mg/day (M±m). 80% RA pts were taking DMARDs: most of them - methotrexate (45%) and leflunomide (21%). All patients were taking NSADs. MDD was diagnosed by psychiatrist in accordance with the DSM-IV after structured interview. Psychiatric scales used: Hospital Anxiety and Depression Scale, Perceived Stress Scale (PSS-10) and projective psychological methods for affectivity (anxious, melancholic or apathetic) type detection. We studied also the history of stressful life events before and during RA and adverse childhood experiences (ACEs) that included childhood (up to 11 years age) physical, emotional or sexual abuse; witnessing domestic violence; growing up with household substance abuse, mental illness, parental death or divorce (parental deprivation) and/or an incarcerated household member. Fatigue was evaluated using Fatigue Severity Scale (FSS). The Brief Pain Inventory (BPI) was used for pain assessment. Results: Stressful life events preceded the RA onset in 97 (77, 6%) pts and the RA exacerbations in 76 (60, 8%) pts. ACEs, the parental deprivation most often, were reported by 97 (77, 6%) RA pts. MDD was diagnosed in 43 (34.4%) RA pts. All RA pts with MDD had stressful life events history and ACEs. The factors associated with MDD were found during Pearson correlations. Then linear regression analysis was done and obtaining prognostic model showed that MDD was associated with ACEs (β=0, 096), stressful life events before RA onset (β=0, 303), apathetic or melancholic affects (β=0, 179), such inflammatory factors as blood platelets number (β=0, 338), swollen joints count (β=0, 143), RA exacerbations number (β=0, 123), the most intensive pain (BPI-max) (β=0, 075) and fatigue (FSS≥4) (β=0, 215) (area under the ROC curve =0, 912). Conclusions: MDD in RA pts connected first of all with stressful life events and associated with more intensive inflammatory signs, pain and fatigue. The results have confirmed studies on the impact of early and subsequent life stress on inflammatory responses which is biological basis of RA and MDD. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2151